Membrane disruption and cytotoxicity of hydrophobic N-alkylated imino sugars is independent of the inhibition of protein and lipid glycosylation. - Mellor, H; Platt, F; Dwek, R; Butters, T (2003)
The N-alkyl moiety of N-alkylated imino sugars is crucial for therapeutic activities of these compounds as inhibitors of glycosphingolipid (GSL) biosynthesis and as antivirals. The improved potency afforded by a long N-alkyl moiety is coincident with increased compound-induced cytotoxicity. Therefore, in the present study, we examined the mechanism of this cytotoxicity in detail. Despite N-butyl-deoxynojirimycin and N-butyl-deoxygalactonojirimycin inhibiting the glycosylation of ceramide to glucosylceramide, ceramide levels did not increase in HL60 cells treated with these compounds. Long-chain N-alkylated imino sugars were toxic to cells at concentrations considerably lower than the critical micellar concentrations for these compounds and consequently did not solubilize radioactively labelled cellular proteins and lipids. However, membrane disruption and cell fragmentation did increase in a concentration- and chain-length-dependent manner. These results are consistent with previously proposed interactions between surface-active amphiphiles and protein-containing lipid membranes when drug concentrations are below the critical micellar concentration. Taken together, these results demonstrate that the cellular toxicity of hydrophobic N-alkylated imino sugars is due to cell lysis and cell fragmentation and, most importantly, is not related to the beneficial therapeutic effects of these compounds on protein and in lipid glycosylation. This information will aid in the future development of more selective imino sugar therapeutics for the treatment of human disease.